Mannan binding lectin-associated serine protease-2 (MASP-2) critically contributes to post-ischemic brain injury independent of MASP-1. Issue 1 (December 2016) - Orsini, Franca; Chrysanthou, Elvina; Dudler, Thomas; Cummings, W. Jason; Takahashi, Minoru; Fujita, Teizo; Demopulos, Gregory; De Simoni, Maria-Grazia; Schwaeble, Wilhelm
Abstract Background Complement activation via the lectin activation pathway (LP) has been identified as the key mechanism behind post-ischemic tissue inflammation causing ischemia-reperfusion injury (IRI) which can significantly impact the clinical outcome of ischemic disease. This work defines the contributions of each of the three LP-associated enzymes—mannan-binding lectin-associated serine protease (MASP)-1, MASP-2, and MASP-3—to ischemic brain injury in experimental mouse models of stroke. Methods Focal cerebral ischemia was induced in wild-type (WT) mice or mice deficient for defined complement components by transient middle cerebral artery occlusion (tMCAO) or three-vessel occlusion (3VO). The inhibitory MASP-2 antibody was administered systemically 7 and 3.5 days before and at reperfusion in WT mice in order to assure an effective MASP-2 inhibition throughout the study. Forty-eight hours after ischemia, neurological deficits and infarct volumes were assessed. C3 deposition and microglia/macrophage morphology were detected by immunohistochemical, immunofluorescence, and confocal analyses. Results MASP-2-deficient mice (MASP-2−/− ) and WT mice treated with an antibody that blocks MASP-2 activity had significantly reduced neurological deficits and histopathological damage after transient ischemia and reperfusion compared to WT or control-treated mice. Surprisingly, MASP-1/3−/− mice were not protected, while mice deficient in factor B (fB−/− ) showed reduced neurological deficits compared to WT mice. Consistent with behavioral and histological data, MASP-2−/− had attenuated C3 deposition and presented with a significantly higher proportion of ramified, surveying microglia in contrast to the hypertrophic pro-inflammatory microglia/macrophage phenotype seen in the ischemic brain tissue of WT mice. Conclusions This work demonstrates the essential role of the low-abundant MASP-2 in the mediation of cerebral ischemia-reperfusion injury and demonstrates that targeting MASP-2 by an inhibitory therapeutic antibody markedly improved the neurological and histopathological outcome after focal cerebral ischemia. These results contribute to identifying the key lectin pathway component driving brain tissue injury following cerebral ischemia and call for a revision of the presently widely accepted view that MASP-1 is an essential activator of the lectin pathway effector component MASP-2.